If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3 + u) = 0 (3 * 6 + u * 6) = 0 (18 + 6u) = 0 Solving 18 + 6u = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6u = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6u = 0 + -18 6u = 0 + -18 Combine like terms: 0 + -18 = -18 6u = -18 Divide each side by '6'. u = -3 Simplifying u = -3
| y=-10(0)+18 | | 24=7x+3-4x | | 16n+8=2(8n+4) | | 0=2p^2+3p | | x^2+21+20=0 | | (6y^2+1)dy=4dx | | -(1+7x)+4(6x+1)=36 | | x(20-2x)=40 | | -4v=-44 | | 20=9x+5-4x | | 5x-8=2x+1+2x-9 | | 4z+3=16 | | 4x+6=-4+78 | | -9m+7=88 | | 3.2=8.8-0.7x | | -12=3d | | 2(9+y)+5y=4 | | 2x-7+9x+11=2(3x+2) | | 10d-8=32 | | -2y+8=-2(2y+2) | | -66=6-6f | | 2.9+10m=7.72 | | 2x=(y-x) | | 6+4b=-3 | | h/4=-8 | | 4x-6x=11+5 | | 6+8c=-2 | | 160=2(x+26) | | 7(x+7)+4=53 | | 15x^5=6x^3 | | 2(-4)+5y=4 | | 10x+5-4x=35 |